2017
DOI: 10.1007/s11999-016-4770-y
|View full text |Cite
|
Sign up to set email alerts
|

Can Preoperative Patient-reported Outcome Measures Be Used to Predict Meaningful Improvement in Function After TKA?

Abstract: Background Despite the overall effectiveness of total knee arthroplasty (TKA), a subset of patients do not experience expected improvements in pain, physical function, and quality of life as documented by patient-reported outcome measures (PROMs), which assess a patient's physical and emotional health and pain. It is therefore important to develop preoperative tools capable of identifying patients unlikely to improve by a clinically important margin after surgery.Questions/purposes The purpose of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
189
7
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 223 publications
(209 citation statements)
references
References 49 publications
12
189
7
1
Order By: Relevance
“…26,38 Along with our results, other studies have noted that despite TKA’s cost-effectiveness, 1,2 many patients may not achieve significant improvement in physical function as measured by PRO change score. 15,39 In our work, 37% of surgeries did not result in clinically significant improvement in physical function. Future research should explore whether patient satisfaction has any relationship with their reported physical function improvement.…”
Section: Discussionmentioning
confidence: 42%
See 4 more Smart Citations
“…26,38 Along with our results, other studies have noted that despite TKA’s cost-effectiveness, 1,2 many patients may not achieve significant improvement in physical function as measured by PRO change score. 15,39 In our work, 37% of surgeries did not result in clinically significant improvement in physical function. Future research should explore whether patient satisfaction has any relationship with their reported physical function improvement.…”
Section: Discussionmentioning
confidence: 42%
“…19 Our AUC model values of 0.81 and 0.80 improve on another medical center’s model for PCS improvement of 5 points at 1 year, which had a multivariate predictive AUC value of 0.71 with fewer variables. 15 That model included SF-12 PCS and MCS, gender, age, and race. In a sub-analysis, we matched their variables to our data with only 1-year PCS follow-up measures and achieved an AUC of 0.77 (95% CI 0.73–0.81) (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations